PENGARUH PRENATAL MASSAGE TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI KLINIK ERNA KECAMATAN PADANG BOLAK KABUPATEN PADANG LAWAS UTARA - YENI ZAHARA HARAHAP (LP2MTBM MAKARIOZ, 2019)
One complaint that is often experienced by third trimester pregnant women is that back pain is caused by the increased heavy burden carried by the mother, the baby in the womb (Walyani. 2015)The results of research conducted by Arum Sariati (2017) on